PENGARUH PELATIHAN PUBLIC SPEAKING TERHADAP PENINGKATAN SOFT SKILL SISWA DI SMKN 17 JAKARTA - Ria Restina Robiyanti; Tatik Purwaningsih; Arnold Surya Nugroho; Dharmika Pranidhi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study aims to determine the effect of public speaking training on improving students' soft skills at SMKN 17Jakarta. The background of this research is based on the importance of soft skills, such as effectivecommunication, confidence, and teamwork in supporting students' readiness to face the world of work. Theresearch method used is a quantitative approach with a pre-experimental design of the one-group pretest-posttesttype. The research sample amounted to 60 students in grades X to XII who were selected using the purposivesampling technique. The research instrument is in the form of a soft skill questionnaire that has been tested forvalidity and reliability. Data analysis using a paired sample t-test with the help of SPSS version 26. The resultsshowed that there was a significant difference between students' soft skill scores before and after participating inpublic speaking training. The average student soft skill score increased from 68.45 during the pretest to 82.17during the posttest. The results of the t-test showed a significance value of 0.000 (p < 0.05), which means thatpublic speaking training has a significant effect on improving students' soft skills. Thus, this training has provento be effective in developing important aspects of soft skills, especially in terms of verbal communication,confidence, and social interaction skills. Based on these findings, it is recommended that public speaking trainingbe made a continuous program in schools to support the holistic development of students' character andcompetencies. Follow-up research is also recommended involving control variables to test their long-term effects.Keywords: Public Speaking, Soft Skills, Communication, Confidence